The relationship among depressive symptoms, urgency, and problematic alcohol and cannabis use in community adults. (January 2019) - Um, Miji; Hershberger, Alexandra R.; Cyders, Melissa A.
Abstract: Background: This study examined alternative models for how negative and positive urgency influence the relationship between depressive symptoms and alcohol and cannabis use in a community sample. Methods: Participants included adults ( n = 675; age = 42.57, SD = 15.66; 65.0% female; 74.2% White) in the community sample from the Rockland Project by the Nathan Kline Institute. Path analyses were conducted. Results: Negative urgency was a unique mediator in the relationship between depressive symptoms and problematic alcohol use ( β =0.121, 95% CI = 0.060–0.182) and problematic cannabis use ( β =0.120, 95% CI = 0.060–0.179). Negative and positive urgency significantly moderated the relationship between depressive symptoms and problematic cannabis use (negative urgency: β = 0.092, 95% CI = 0.040–0.145; positive urgency: β = 0.070, 95% CI = 0.022–0.119), such that the relationship was positive at high levels and negative at low levels of urgency. The patterns and levels of the relationships between depressive symptoms and cannabis use differed between negative and positive urgency. Neither urgency trait moderated the relationship between depressive symptoms and problematic alcohol use. Conclusions: Despite being strongly related, negative and positive urgency have distinct roles in the relationship between depressive symptoms and problematic alcohol and cannabis use. Previous finding with younger samples that do not include both traits in the model at time generalize and at other times do not replicate, which warrants the continued examination of how these traits impart risk across the lifespan. Highlights: Negative urgency explained the relationship between depression and substance use. Urgency level did not affect the association between depression and alcohol use. Higher urgency was related to a stronger depression – cannabis use relationship. The relationship patterns diverged across negative and positive urgency.